PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN OPPO F1SSELFIE EXPERT SMARTPHONE (Study Empiris pada Pusat Penjualan Handphonedi Matahari Simpang Lima Semarang) - Septiawan Tri Arsandi, 14.05.51.0186 (Students' Journal of Economic and Management, 2017)
This study aimed to analyze the effect of product quality, price and brand image perceptions on purchase decisions Oppo F1s Selfie Smartphone Expert in Semarang. The population studied in this research is that consumers buy Oppo F1s Selfie Smartphone Expert in Sales Center phone Solar Semarang Simpang Lima. The minimum sample size in penelitianini, the number of indicators of research as much as 18 so that the number of samples is 5 times the number of indicators or as many as 5 x 20 = 100. The sampling technique used Proposive Sampling. The analysis tool used is the test of validity, reliability, multiple linear regression. The results of the analysis can be concluded that: The product quality has positive influence on purchase decisions. Perception price positive influence on purchase decisions. Brand image positive influence on purchasing decisions Keywords: product quality, price perception, brand image and purchasing decisions